حاسن الشورى وإشكالية لزومها في النظام السياسي الإسلامي - حامدي, عبد الكريم (University of Eloued جامعة الوادي, 2007)
تشكل الشورى أحد المبادئ الهامة في نظام الحكم في الإسلام أمر بها القرآن الكريم وعمل بها رسول الله  والخلفاء من بعده لما فيها من المحاسن الكثيرة، لكنها أهملت على أيدي الخلفاء الأمويين مما كان له أثر سيء بعلاقة الحاكم بالمحكوم وأدى ذلك إلى ضعف الأمة وانقسامها إلى طوائف وفرق . واليوم تسعى الدول العربية الإسلامية إلى استعادة الشورى في أنظمتها البرلمانية متأثرة بالديمقراطية الغربية، لكن الإشكال المطروح قديما وحديثا هل الشورى واجبة ابتداء وانتهاءً ؟ أي هل يجب عليه أن يستشير أعضاء الحكومة والبرلمان وهل عليه أن يأخذ بنتائج الشورى أم أن ذلك غير واجب هذا ما يعالجه هذا البحث. The summary: The council or advice (Eshourah in arabic)is one of the main principles of the political system in Islam. The holy Qur’an ordered muslims to parctice Eshourah. The prophet – peace be up on him- and the calipgs after him practiced Eshourah. But, it was neglected by the Amawian’s caliphs (the caliphs from the tribe of bany oumaia), which let a very bad effects on the relationship between the governors and the people. Thus, the Ummah get more and weak and separated into several parts and groups. Nowadays, the Islamic and Arabic stats work to take back again Eshouah in their parliamentary systems, influenced by the occidental democracy. The asked questions about this subject- in the past and now- are: Is it obligatory to practice Eshourah ? Is the governor obliged to practice Eshourah with the members of the government and the parlaiment? Is he obliged to take in consideration the results of Eshourah or not? These are the main themes treated in this research.
مقال بمجلة البحوث والدراسات
Keywords: شورى - نظام حكم - الإسلام - نظام سياسي